Intervention Fidelity: An Essential Component for Understanding ASD Parent Training Research and Practice. (16th September 2013) - Wainer, Allison; Ingersoll, Brooke
Abstract : Previous research has explored the efficacy and effectiveness of autism spectrum disorder (ASD) parent training interventions. Recent trials of such programs have not replicated earlier compelling outcomes, yet the reasons for the failure of such programs to produce desired effects are unclear. The purpose of the current article is to discuss the role of intervention fidelity in elucidating the relationships between a parent training program, the implementation and sustainability of an intervention, and important child outcomes. The article will discuss the importance of assessing intervention fidelity for the identification and successful use of effective treatment strategies and will propose an integrative conceptual framework for approaching the study and evaluation of intervention fidelity with respect to ASD parent training programs.